2023
DOI: 10.5530/pj.2023.15.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Channa striata Extract on Serum Albumin and High Sensitive C-Reactive Protein in End-Stage Renal Disease Patients: A Randomized Controlled Trial

Abstract: Background: Albumin is a marker of nutritioinal inflammation and mortality. Chronic inflammation, as indicated by the concentration of a proinflammatory cytokine, high sensitivity C-reactive protein (hs-CRP) was reported to be high in end-stage renal disease (ESRD) patients. Channa striata (CS) contains high protein that can increase albumin levels and has anti-inflammatory effects. This study was conducted to determine the effect of CS extract on serum albumin and hs-CRP on ESRD patients. Methods: This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In assessing serum albumin levels, it was found that the group receiving CS extract supplementation did not experience a decrease in albumin levels after treatment (2.76 + 0.41 versus 2.76 + 0.40) compared to controls, who experienced a statistically significant decrease (2.78 + 0.38 gr/dl to 2.56 + 0.37). According to previous studies, CS extract increased serum albumin levels in ESRD patients (Putranto et al, 2023). Meanwhile, the use of CS extract in other critical diseases (e.g., stroke) may increase albumin levels after CS supplementation (Kasim et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In assessing serum albumin levels, it was found that the group receiving CS extract supplementation did not experience a decrease in albumin levels after treatment (2.76 + 0.41 versus 2.76 + 0.40) compared to controls, who experienced a statistically significant decrease (2.78 + 0.38 gr/dl to 2.56 + 0.37). According to previous studies, CS extract increased serum albumin levels in ESRD patients (Putranto et al, 2023). Meanwhile, the use of CS extract in other critical diseases (e.g., stroke) may increase albumin levels after CS supplementation (Kasim et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have reported that Channa striata (CS) albumin extract has antiinflammatory and antioxidant effects and can stabilize PAI-1 levels in sepsis patients because it also contains chitosan and glutathione (Hu et al, 2021;Putranto et al, 2023). In assessing serum albumin levels, it was found that the group receiving CS extract supplementation did not experience a decrease in albumin levels after treatment (2.76 + 0.41 versus 2.76 + 0.40) compared to controls, who experienced a statistically significant decrease (2.78 + 0.38 gr/dl to 2.56 + 0.37).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations